ANALISIS KECERNAAN DAN PEMANFAATAN NUTRIEN PAKAN YANG MENGANDUNG TEPUNG KEPALA UDANG PADA KERAPU BEBEK (CROMILEPTES ALTIVELIS) - Ridwan, Ridwan; Puspasari, Andi Idris (Journal Galung Tropika, 2014)
This research was aimed at finding out the effect of the shrimp head meal (SHM) content found in the feed on the nutrient digestibility and utilization of humpback grouper. The research was conducted in floating net cages, and it was arranged in a completely randomized triplicate designs. The treatments in this research were the SHM contents (0 %, 10 %, 20 %, 30 %, and 40 %) found in isonitrogenous and isocaloric diets. The data of each observed variable were analysed by using a one-way analysis of variance (ANOVA) in order to identify the effects of treatments on the nutrient digestibility and utilization. The difference in the treatment effects were determined by Duncan’s multiple range test at significance level of 0.05. The result of the research revealed that the protein digestibility in control diet was not significantly different from that of the diet containing SHM 10%. The protein digestibility decreased in the diets containing SHM of 20% to 40%. Meanwhile, the highest lipid digestibility was resulted from the control diet, and it decreased when SHM contents of the diets increased. The protein utilization (the protein retention and the protein efficiency ratio) and the feed efficiency (the feed conversion ratio) in the fish fed with control diet were not significantly different from those in the fish fed with the diet containing SHM of 10%. The decrease of the protein utilization and feed efficiency started to appear when the diet content of SHM had reached the level of 20%. The highest lipid retention was resulted from the control diet. The decrease of lipid retention started to appear when the diet content of SHM had reached the level of 10%. Based on the results, 10% of SHM could be included to the diet without any reduction in the protein digestibility and utilization and feed efficiency of humpback grouper.